2009
DOI: 10.1007/s10858-008-9295-6
|View full text |Cite
|
Sign up to set email alerts
|

Automated protein structure calculation from NMR data

Abstract: Current software is almost at the stage to permit completely automatic structure determination of small proteins of < 15 kDa, from NMR spectra to structure validation with minimal user interaction. This goal is welcome, as it makes structure calculation more objective and therefore more easily validated, without any loss in the quality of the structures generated. Moreover, it releases expert spectroscopists to carry out research that cannot be automated. It should not take much further effort to extend automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 84 publications
0
43
0
Order By: Relevance
“…A ccurate and fast validation of protein structures constitutes a long-standing problem in NMR spectroscopy (1)(2)(3). Investigators have proposed a plethora of methods to determine the accuracy and reliability of protein structures in recent years (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…A ccurate and fast validation of protein structures constitutes a long-standing problem in NMR spectroscopy (1)(2)(3). Investigators have proposed a plethora of methods to determine the accuracy and reliability of protein structures in recent years (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Improving the stereochemical quality Williamson and Craven (2009) have described the effectiveness of explicit solvent refinement of NMR structures and suggest that it should be a standard procedure. For protein structures that have regions of high mobility/uncertainty due to few or no NOE observations, we have successfully employed a hybrid protocol from XPLOR-NIH that incorporates thin-layer water refinement (Linge et al, 2003) and a multidimensional torsion angle database (Kuszewski et al, 1996(Kuszewski et al, , 1997.…”
Section: Alipanahi Et Almentioning
confidence: 99%
“…Simulated annealing by torsion angle dynamics became the standard method to calculate NMR protein structures. A recent survey ( Table 1 in [30]) revealed that the structure calculation programs that are cited most often in the NMR protein structures deposited to the Protein Data Bank [5] When the basic problem of NMR protein structure calculation was solved satisfactorily by these programs, interest turned towards automating the most time-consuming part of NMR spectral analysis, namely the assignment of multidimensional NOESY spectra for the collection of conformational restraints. Because of the extensive degeneracy of the chemical shifts this task is cumbersome and error-prone if done manually.…”
Section: Historical Developmentmentioning
confidence: 99%
“…Network anchoring reduced the initial ambiguity of NOESY cross-peak assignments by inducing self-consistency with the network of other assigned NOEs, and constraint combination minimised the impact of erroneous distance restraints on the resulting structure. At present, the combination of the automated assignment of NOESY cross-peaks and the structure calculation with CYANA or ARIA have become the standard approach to protein structure analysis by NMR [30]. Alternative approaches for the automated assignment of NOESY cross-peaks were implemented in the AutoStructure [33], PASD [43], and KNOWNOE [44] algorithms, and in a Bayesian approach [45].…”
Section: Historical Developmentmentioning
confidence: 99%